2002
DOI: 10.1038/sj.onc.1205492
|View full text |Cite
|
Sign up to set email alerts
|

Sequential extension of proliferative lifespan in human fibroblasts induced by over-expression of CDK4 or 6 and loss of p53 function

Abstract: Replicative senescence is thought to be a signi®cant barrier to human tumorigenesis, which in human ®bro-blasts, and many other cell types, can be overcome experimentally by combined loss of function of p53 and Rb`pathways'. To avoid the confounding pleiotropic e ects of HPVE7 frequently used in such studies, here we have employed retroviral vectors over-expressing CDK4 or CDK6 as a more representative model of naturally-occurring mutations targeting the Rb pathway. We show that these can extend ®broblast life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
4
28
1
Order By: Relevance
“…Wynford-Thomas (Morris et al, 2002) has recently reported that a Cdk4 mutant, R24C, was unable to cooperate with hTERT to immortalize normal human keratinocytes, and in addition resulted in the production of so much functional p53 that inactivating it was also required before the cells became immortal (Morris et al, 2002). This apparent contradiction of our current results can be explained by the different properties of wild-type and mutant Cdk4s.…”
Section: Discussioncontrasting
confidence: 97%
“…Wynford-Thomas (Morris et al, 2002) has recently reported that a Cdk4 mutant, R24C, was unable to cooperate with hTERT to immortalize normal human keratinocytes, and in addition resulted in the production of so much functional p53 that inactivating it was also required before the cells became immortal (Morris et al, 2002). This apparent contradiction of our current results can be explained by the different properties of wild-type and mutant Cdk4s.…”
Section: Discussioncontrasting
confidence: 97%
“…If both pRb and p53 are inactivated, the cells proliferate until they reach the M2 phase of senescence where continued cell proliferation is offset by cell death (13,14). If only one of the tumor suppressor pathways is disabled, then HDFs senesce at a stage that is operationally between M1 and M2, referred to as M INT or M1.5 (18)(19)(20). In line with these ideas, we have previously shown that p16…”
Section: More Specifically P16mentioning
confidence: 84%
“…While the CDK4(R24C) mutated form appears exclusively in some cases of sporadic and familial melanomas (Ohta et al, 1994;Wo¨lfel et al, 1995;Zuo, 1996;Soufir et al, 1998), amplification and/or overexpression of CDK4 have been found in a wide spectrum of human tumors (He et al, 1995;Holland et al, 1998;Kanoe et al, 1998;Nikitakis et al, 2002). Surprisingly, Morris et al (2002) have shown that the CDK4(R24C) produced no additional growth advantage compared with CDK4 overexpressing forms in human fibroblasts; indeed CDK4(R24C) was less effective than wild-type CDK4 (Morris et al, 2002). These results support the observation that CDK4(R24C) mutation is restricted to melanoma development where escape of the p16 Ink4a inhibitory effect appear to be indispensable, while overexpression of CDK4 may be a more general mechanism for an acquired growth advantage (He et al, 1994;Schmit et al, 1994;Sonoda et al, 1995;Kanoe et al, 1998;An et al, 1999;Dei Tos et al, 2000;Lam et al, 2000).…”
Section: Discussionmentioning
confidence: 99%